ANALISIS USAHATANI JAMUR TIRAM DI GAMPONG PANGGOI KECAMATAN MUARA DUA KOTA LHOKSEUMAWE (Studi Kasus: Usahatani Jamur Tiram Bapak Safwandi) - Iga Mayada; Muhammad Authar; Martina Martina (Jurnal Mahasiswa Agribisnis, 2024)
Oyster mushroom is one type of consumption mushroom that has high nutritional value and economic value. This research was conducted in Gampong Panggoi Muara Dua District, Lhokseumawe City, precisely at Mr. Safwandi's oyster mushroom business. The purpose of this study is to determine the amount of profit obtained from Safwandi's Oyster Mushroom Farm in Gampong Panggoi Muara Dua District, Lhokseumawe City. To analyze the feasibility of Safwandi's Oyster Mushroom Farm in Gampong Panggoi District Muara Dua Lhokseumawe City analyzing profits. To analyze the constraints that exist on Safwandi's Oyster Mushroom Farm in Gampong Panggoi District Muara Dua Lhokseumawe City. Determination of the location and object of research is done intentionally. The data used are primary data and secondary data. This study uses quantitative descriptive and qualitative descriptive data analysis methods. The results of this study indicate that Mr. Safwandi's oyster mushroom farm obtained a profit of Rp.35,283,336,-/year with the use of production costs incurred Rp.34,916,664,-/year and revenue costs of Rp.70,200,000,-/year. Mr. Safwandi's oyster mushroom farm is feasible to cultivate because the production BEP value is 698 kg, the price BEP value is Rp.24,869/kg, the R/C ratio value is 2.01, the B/C ratio value is 1.01 and the ROI value is 101%. The constraints faced by Mr. Safwandi's oyster mushroom farm are (1) Labor (2) Capital (3) Pests and Diseases (4) Raw Materials Keywords: Profit, Feasibility, Business Constraints.